Advanced vasospasm in carotid stenting using the distal filter-type embolic protection device: A case report - Yabalak, Ahmet; Yılmaz, Murat (Journal of Surgery and Medicine, 2021)
There are difficulties in the use of embolic protection devices (EPD) for carotid artery stenting (CAS), and various side effects can be observed. We presented a patient who underwent CAS with a distal filter-type (DF) EPD for symptomatic right internal carotid artery (ICA) stenosis and showed advanced vasospasm. A 68-year-old male patient was hospitalized with a pre-diagnosis of transient ischemic attack (TIA) in the form of left-sided weakness. Computed tomography angiography revealed 90% stenosis in the right ICA. On the 5th day, he underwent an angiography, which showed a plaque causing 90% stenosis. A 5F Spider FX (Medtronic Corp.; Minneapolis, MN, USA) was placed in the cervical ICA. At this time, mild vasospasm was observed in the cervical ICA, but the flow was normal. After pre-dilatation, a Protégé 8-6x40 stent was placed in the stenotic segment. Due to the 50% residual stenosis, a post-dilatation was performed. After post-dilatation, advanced vasospasm developed distal to the stent and the flow was completely obstructed. Vasospasm significantly regressed within a few minutes with intra-arterial nitrate administration. There was no change in the neurological examination of the patient during and after the procedure. Although vasospasm is usually a self-limiting complication that resolves without clinical symptoms, it may cause a TIA or an infarct. In CAS procedures, the possibility of a vasospasm should be kept in mind and if it occurs, the irritant should be removed. If there is no improvement, an intra-arterial vasodilator should be administered.